A neutral, acyclic, borataalkene-like ligand for group 11 metals: L- and Z-type ligands side by side. Issue 24 (3rd March 2022) - Krämer, Felix; Radius, Michael; Berberich, Helga; Fernández, Israel; Breher, Frank
Abstract : Side by side! An α-borylated phosphorus ylide can act as L- and Z-type ligand side by side. A detailed experimental and computational study provides evidence for a tuneable L/Z-ratio by varying the metal fragments and/or the boron substituents. Abstract : The overall neutral α-borylated phosphorus ylide Ph3 PC(Me)BEt2 behaves like a polar borataalkene and can act as acyclic, ambiphilic π-type ligand with L- and Z-type functionalities side by side. In the complexes [MX{η 2 -Ph3 PC(Me)BEt2 }] (M = Cu, (Ag), Au; X = Cl, NTf2 ), the bonding is dominated by the highly nucleophilic ylidic carbon atom (L-type ligand). The Lewis acidic boron atom furnishes nonetheless a small but significant bonding contribution (Z-type ligand).